The CIO playbook strategies and best practices for IT leaders to deliver value - Colisto, Nicholas R., 1966- (Wiley, 2012)
"This book offers insightful and practical advice and strategies to help IT leaders maximize the impact of IT on their business. While the technologies constantly change at a dramatic pace, the practices described in this book are timeless and can help transform IT department from a mere order taker to a high performance organization that delivers extraordinary business outcomes, despite this era of turbulent economic challenges.The author shares a framework that he has developed over his 25 year career that includes practical strategies and tactics to help IT leaders truly transform their organizations. The framework involves seven steps: (1) partner, (2) innovate, (3) deliver, (4) support, (5) optimize, (6) protect, and (7) grow. Interviews with CIOs and technology leaders from companies such as HBO, Hyatt, and Conair will be used to help support the framework"--